Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4103/njms.njms_16_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of intermaxillary fixation screws versus modified arch bar for intermaxillary fixation

Abstract: Aim:This study aimed to evaluate the efficacy of intermaxillary fixation (IMF) screws and modified arch bar.Materials and Methods:This study is a randomized clinical trial in which all participants were divided into two groups of ten in each group and designated as Group A and Group B. In Group A, IMF was achieved by the use of four to six 2×8mm stainless steel IMF screws. In Group B, IMF was achieved by modified screw arch bar.Results:In the present study, a total of twenty patients were analyzed. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Mean OHI difference for the Group B (0.54±0.12) was significantly lower to A (1.11±029). Rothe et al 11 calculated OHI scores, at immediate postoperative period, after 15 days, 30 days, and 45 days and found that maximum hygiene was maintained in IMF screw group.…”
Section: Discussionmentioning
confidence: 99%
“…Mean OHI difference for the Group B (0.54±0.12) was significantly lower to A (1.11±029). Rothe et al 11 calculated OHI scores, at immediate postoperative period, after 15 days, 30 days, and 45 days and found that maximum hygiene was maintained in IMF screw group.…”
Section: Discussionmentioning
confidence: 99%